2013
DOI: 10.1007/s11356-013-2188-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth and yield losses in two Zea mays L. cultivars (quality protein maize and nonquality protein maize) under projected levels of ozone

Abstract: Rapid industrialization and economic developments have increased the tropospheric ozone (O3) budget since preindustrial times, and presently, it is supposed to be a major threat to crop productivity. Maize (Zea mays L.), a C4 plant is the third most important staple crop at global level with a great deal of economic importance. The present study was conducted to evaluate the performance of two maize cultivars [HQPM1: quality protein maize (QPM)] and [DHM117: nonquality protein maize (NQPM)] to variable O3 dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…For soybean we found a sensitivity to W126 of 0.45% ppm −1 h −1 compared with 0.4% ppm −1 h −1 (27) and 1.7% ppm −1 h −1 (28), and a sensitivity to AOT40 of 0.49% ppm −1 h −1 compared with 0.5-1% ppm −1 h −1 (2,30,31). For maize we found a sensitivity to W126 of 0.52% ppm −1 h −1 compared with 0.12% ppm −1 h −1 (27) and 0.7% ppm −1 h −1 (29), and a sensitivity to AOT40 of 0.62% ppm −1 h −1 compared with 0.4% ppm −1 h −1 (2) and 0.5% ppm −1 h −1 (32). Thus, the sensitivity estimates produced by the current study for the two species are in line with previously reported values.…”
Section: Discussionmentioning
confidence: 68%
“…For soybean we found a sensitivity to W126 of 0.45% ppm −1 h −1 compared with 0.4% ppm −1 h −1 (27) and 1.7% ppm −1 h −1 (28), and a sensitivity to AOT40 of 0.49% ppm −1 h −1 compared with 0.5-1% ppm −1 h −1 (2,30,31). For maize we found a sensitivity to W126 of 0.52% ppm −1 h −1 compared with 0.12% ppm −1 h −1 (27) and 0.7% ppm −1 h −1 (29), and a sensitivity to AOT40 of 0.62% ppm −1 h −1 compared with 0.4% ppm −1 h −1 (2) and 0.5% ppm −1 h −1 (32). Thus, the sensitivity estimates produced by the current study for the two species are in line with previously reported values.…”
Section: Discussionmentioning
confidence: 68%
“…Because of its oxidative capacity, high O 3 levels in the atmosphere are detrimental to living organisms, including plants. Ozone is among the most damaging air pollutants to which plants are exposed, and produces substantive plant biomass and yield (seed weight) reductions (Thompson 1992;Agrawal et al 2005;Manning 2005;Hassan 2006;Hassan and Tewfik 2006;Singh et al 2009aSingh et al , 2014Wahid 2006 a, b;Sarkar and Agrawal 2010a, b;Tripathi and Agrawal 2013). The economic loss for 23 horticultural and agricultural crops from O 3 exposure was estimated to be approximately $6.7 billion for the year 2000 in Europe (Holland et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Maize plants were grown on ground inside OTCs of diameter 2.5 m and height 2.5 m which were installed as described elsewhere . Detailed description about the characteristics of selected maize cultivars, raising of plants and fertilizer dosages has been given in Singh et al . Maize plants were grown under four treatment regimes, i.e.…”
Section: Methodsmentioning
confidence: 99%